2016
DOI: 10.1111/hdi.12467
|View full text |Cite
|
Sign up to set email alerts
|

Plasma vitamin C levels in ESRD patients and occurrence of hypochromic erythrocytes

Abstract: This finding supports the hypothesis that vitamin C mobilizes iron stores, improves iron delivery to the bone marrow, and increase the fraction of RBC with normal Hb content. Further research is warranted on development of protocols for safe and effective use of supplemental vitamin C for management of renal anemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
(63 reference statements)
1
5
0
Order By: Relevance
“…Studies in dialysis patients have shown that vitamin C supplementation may lead to decreased serum ferritin levels [22], which is consistent with storage iron mobilization. These reports are supported by previously reported data from several studies [2228] and confirmed in a recently published meta-analysis by Deved and colleagues [29]. Our data on the correlation between hemoglobin and vitamin C supports this association and the claims made by Deved and others on the importance of considering the prescription of vitamin C in anemia management (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Studies in dialysis patients have shown that vitamin C supplementation may lead to decreased serum ferritin levels [22], which is consistent with storage iron mobilization. These reports are supported by previously reported data from several studies [2228] and confirmed in a recently published meta-analysis by Deved and colleagues [29]. Our data on the correlation between hemoglobin and vitamin C supports this association and the claims made by Deved and others on the importance of considering the prescription of vitamin C in anemia management (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…7d ). Many researchers have shown that the bone marrow is the major site of erythropoiesis in humans and mice 41 43 . Additionally, a low Hb content per RBC is the result of an insufficient iron content in the bone marrow during erythropoiesis 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers have shown that the bone marrow is the major site of erythropoiesis in humans and mice 41 43 . Additionally, a low Hb content per RBC is the result of an insufficient iron content in the bone marrow during erythropoiesis 43 . This information implied that thiram suppresses bone marrow activity resulting in decreased production of RBCs and that thiram also inhibits angiogenesis by disrupting the blood supply in tibial chondrocytes, which will seriously affect growth and development of the tibial growth plate.…”
Section: Discussionmentioning
confidence: 99%
“…Serum ascorbate levels are inversely correlated with the osmotic fragility of red cells and moreover, in patients with diabetes, lower erythrocyte ascorbate levels are associated with increased RBC rigidity (69). Similarly, in patients with end-stage renal disease, low serum vitamin C levels correlate with hypochromic red cells whereas patients with high vitamin C levels harbor an increased fraction of red cells with normal hemoglobin content (88). These correlative studies are in agreement with ex vivo erythropoiesis assays showing that vitamin C promotes the erythroid differentiation of human hematopoietic progenitors (17).…”
Section: Discussionmentioning
confidence: 99%